2012
DOI: 10.1002/jso.23305
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary hepatopancreatobiliary small cell carcinoma

Abstract: Surgical resection was associated with prolonged survival for patients with localized pancreatic, gallbladder, and biliary primaries. While we recognize several biases inherent in a population-based study, these results provide insight into the survival that can be achieved with surgical resection of SCC in these specific locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…[ 15 20 ] Primary small cell carcinoma, although rare, could be seen in the pancreas and should be included in the differential diagnosis metastatic small cell carcinoma. [ 15 33 34 ] Prior history of lung cancers including SCLC would be of great help for suggesting a metastasis. All of our patients with metastatic lung cancer had an either prior history or current biopsy to suggest a lung primary.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 20 ] Primary small cell carcinoma, although rare, could be seen in the pancreas and should be included in the differential diagnosis metastatic small cell carcinoma. [ 15 33 34 ] Prior history of lung cancers including SCLC would be of great help for suggesting a metastasis. All of our patients with metastatic lung cancer had an either prior history or current biopsy to suggest a lung primary.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical treatment of hgPNEC is controversial because most patients experience recurrent disease, reports discuss a beneficial effect of surgical treatment on survival. [10][11][12][13][14] These studies are either small case reports/series or larger series with lack of a well-defined comparative group.…”
mentioning
confidence: 99%
“…Surgery is the mainstay of GB cancer treatment, but it is unclear whether radical operations produce better outcomes for advanced stages of SCC. Groeschl et al 3 analyzed the SEER (The Surveillance, Epidemiology, and End-Results) database between 1998 and 2008, in a study of hepatopancreatobiliary SCC, and concluded that surgical resection was associated with prolonged survival for patients with localized pancreatobiliary SCC. Of 32 patients with SCC of the GB, 24 (75%) received surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Although there is little experience with radiation for patients with SCC of the GB, it can be considered for use postoperatively, or to ameliorate symptoms, which are caused by an unresected tumor or metastasis. 3 …”
Section: Discussionmentioning
confidence: 99%